2022
DOI: 10.1108/ijmce-06-2021-0068
|View full text |Cite
|
Sign up to set email alerts
|

Examining coaches’ feedback to preservice teacher candidates on a core practice

Abstract: PurposeFor preservice teacher candidates (PSTs), receiving feedback on core practices is an important component in supporting the development of their practice. However, coaches are often underprepared to support PSTs on core practices, and feedback can be infrequent or low quality (Anderson and Stillman, 2013; Clarke et al., 2014). Understanding such variation in the content and process for providing feedback to PSTs is important in evaluating and improving feedback effectiveness for amplifying their learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
0
5
0
1
Order By: Relevance
“…for preparing teacher candidates (Barker, 2012) and consequently, ensuring fidelity of interventions (Cash et al, 2022). In TPPs, modeling occurs when teacher educators demonstrate effective teaching tools (Moore & Bell, 2019).…”
Section: Disabilities (Select One)mentioning
confidence: 99%
See 2 more Smart Citations
“…for preparing teacher candidates (Barker, 2012) and consequently, ensuring fidelity of interventions (Cash et al, 2022). In TPPs, modeling occurs when teacher educators demonstrate effective teaching tools (Moore & Bell, 2019).…”
Section: Disabilities (Select One)mentioning
confidence: 99%
“…This specific praise can help reinforce students' understanding of the course content and students' ability to engage in a professional manner within a team. This feedback enhances students' fidelity in implementing evidence-based practices (EBPs; Cash et al, 2022;Schles & Robertson, 2019). In addition, when teacher candidates are provided with quality feedback on their performance, they learn to provide specific feedback to their students (Cash et al, 2022), an evidence-based practice that promotes desired behaviors by praising students for exhibiting those behaviors (Markelz et al, 2022).…”
Section: Disabilities (Select One)mentioning
confidence: 99%
See 1 more Smart Citation
“…The coach, visiting lecturer or mentor teacher (subsequently referred to as coach) has a direct and discreet link to the teacher via an in-ear speaker and can communicate in real time using either in situ or remote virtual feedback via video observation and a BIE device, with the latter having a minimal effect on the flow of the teaching episode (Horn et al, 2020;Scheeler et al, 2010). The requirement to consistently receive high-quality, practice-related feedback and coaching shapes and develops the careers of all educators; it provides the means to understand what is working well and what needs to be improved (Cash et al, 2022). Research has demonstrated that the timing of performance feedback is critical and often dependent on the task being performed (Hattie and Timperley, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…, 2010). The requirement to consistently receive high-quality, practice-related feedback and coaching shapes and develops the careers of all educators; it provides the means to understand what is working well and what needs to be improved (Cash et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%